Perinatal Mental Health in Kashmir, India During The COVID-19 Pandemic - Shoib, Sheikh (Matern Child Health J, 2020)
The current COVID-19 pandemic in Kashmir along with lockdown measures—ordered to prevent the spread of the disease—has added further trauma to the fragile mental health system in Kashmir. There may be unquantifiable repercussions of the current epidemic on the emotional status of women during the perinatal period. There are numerous challenges in the perinatal period arising out of COVID-19 directly or indirectly because of lockdown measures that has been put in place to prevent the spread of disease.